Changes in soil profile hydraulic properties and porosity as affected by deep tillage soil preparation and Brachiaria grass intercropping in a recent coffee plantation on a naturally dense Inceptisol - Silva, Rodrigo Fonseca da; Severiano, Eduardo da Costa; Oliveira, Geraldo César de; Barbosa, Samara Martins [UNESP]; Peixoto, Devison Souza; Tassinari, Diego; Silva, Bruno Montoani; Silva, Sergio Henrique Godinho; Dias Júnior, Moacir de Souza; Figueiredo, Tomás d'Aquino Freitas Rosa (Elsevier, 2021)
Soil management operations change soil porosity, affecting water infiltration, redistribution, storage, availability, and uptake by plants. Assessing how soil management may affect pore size distribution and hydraulic conductivity is thus highly relevant for rainfed agriculture coping with water shortage. The aim of this study was to assess the effectiveness of tillage treatments, designed to deepen coffee plants root system, on improving structure and physical-hydric attributes of an Inceptisol with a shallow solum. The study was conducted in an experimental area in the municipality of Nazareno, Minas Gerais State, Brazil. Soil samples were collected 18 months after coffee plantation, at different depths (0, 0.25, 0.35, 0.45, 0.55, 0.66, and 0.75 m) and they were used to determine pore-size distribution, saturated and unsaturated hydraulic conductivity. Samples were also collected in surface crusts or in the 0−0.005 m soil layer for detailed grain size analysis. Field water infiltration was measured at different water tensions. Coffee seedlings were planted in rows furrowed to depths depending on tillage treatment: 0.4 m depth, made by a furrow ridger (FP40); 0.6 m depth, made by a subsoiler coupled to a soil preparer mixing the soil to a depth of 0.6 m (FP60); 0.8 m depth, made by a subsoiler and, after mixing the soil to a depth of 0.6 m, by the soil preparer (FP80). The soil between the planting rows was covered by Brachiaria-grass. Soil sampling and field tests were performed in the coffee plants row mechanically treated, in the Brachiaria-grassed inter-row (IR) lane and in a nearby area under natural vegetation (NC). Treatments effects, either mechanical in the coffee rows (FP40, FP 60 and FP80), or biological in the inter-row lane (IR) were compared to reference (NC), representing soil conditions prior to coffee plantation. The FP60 and FP80 treatments improved water infiltration, storage and hydraulic conductivity in the planting rows to a depth of 0.5 m. A more favorable pore size distribution was obtained following these treatments, which improved the soil physical environment. Conversely, furrowing promoted compaction at each implement working depth due to the pressure applied by the rods in the subsurface soil layers, combined with subsoil moisture condition at the time of operations. Root activity of intercropped Brachiaria-grass (IR) improved soil structure, expressed by a favorable pore-size distribution and a faster hydraulic conductivity in the inter-row lane. Similar effects were obtained with FP 60 and FP80 for the coffee rows, where deep furrowing during soil preparation reduced the natural density of the Inceptisol. Therefore, the management strategies tested allowed root deepening and access to soil moisture stored in deeper layers.
Keywords: Geostatistics; Soil hydrodynamic attributes; Soil management; Subsoiling